Features of the movement of Islamic feminism in Kazakhstan: a political analysis (Journal of Philosophy Culture and Political Science, 2024)
Islamic feminism is part of the global movement for women's rights in Muslim societies, and understanding Islamic feminism from a political point of view contributes to deepening its relationship with State institutions, political parties and social movements, which is important for assessing its potential political consequences. The authors of this article consider the role and importance of Islam in the formation of feminist movements in the country, as well as analyze the specific features and challenges faced by Islamic feminists in Kazakhstan. The article highlights the ideological foundations and values underlying Islamic feminism, their relationship with political practice and influence on public structures in Kazakhstan. Through a political analysis, the authors explore the interaction of Islamic feminism with traditional social norms and institutions, as well as its impact on the political sphere of the country. Special attention is paid to the strategies and methods of action of Islamic feminists, their contribution to social transformation and the struggle for gender equality in the context of Kazakh culture and Islamic tradition. The authors draw attention to the prospects for cooperation and interaction between Islamic feminists and other feminist groups and movements in Kazakhstan, their joint efforts in the fight for women's rights and the advancement of women in society. The research aims to identify the main trends in the development of Islamic feminism in Kazakhstan, its impact on public consciousness and the political situation in the country. The methodological basis of the study consists of various research methods, such as: historical method, retrospective analysis, empirical research methods, statistical method and case study, as well as analysis of documentation and legislation. The final analysis will reveal the potential of Islamic feminism as a force capable of making a significant contribution to social and political transformations in Kazakhstan, as well as identify key areas of development of this movement in the future and its impact on the social development of the country. The practical significance of the study lies in the fact that the conclusions can serve as a basis for the development of gender policies and programs in Kazakhstan. Understanding how Islamic feminism affects the status of women and gender equality can help the State adapt its strategies and measures in this area.Key words: Islamic Feminism, Gender Policy, Women's Rights, Religion, Activism, Islam, Gender Equality, Female Status, Feminism, Politics.